Policies Matter: Closing the Reporting and Transparency Gaps in the use of Restraint, Seclusion, and Time-Out Rooms in Schools - Bartlett, Nadine Alice; Ellis, Taylor Floyd (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2021)
Information about the use of physical restraint, seclusion, and time-out rooms in Canadian schools has primarily been anecdotal (media reports and anonymous survey data) due to uneven and non-existent mandates for reporting, transparency and public accountability. The absence of clearly articulated mandates to provide written documentation and publicly available data has allowed this issue to remain obscured from public scrutiny and has severely hampered advocacy efforts for students with disabilities, who are disproportionately impacted. Building upon a prior policy analysis that investigated the policy landscape of physical restraint, seclusion, and time-out in Canadian educational jurisdictions, the current policy analysis explores an additional variable, which was not previously considered, notably the degree to which educational jurisdictions provide clear regulatory requirements to document, report, and review incidents of physical restraint, seclusion, and time-out rooms in schools. Findings indicate that inconsistent reporting requirements have created glaring gaps and loopholes in accountability mechanisms that severely disadvantage students with disabilities. Recommendations include problematizing the institutionalized structures that enable information about the use of restraint, seclusion, and time-out to be filtered and concealed, and identifying guiding principles, which are grounded in research, that can provide a framework for much needed regulatory standards relative to this issue.